Gender Disparity in Return to Education in West Java - Megasari, Diah Nurulia; Purnastuti, Losina (Jurnal Economia, 2016)
Abstract: Gender Disparity in Return to Education in West Java. The investment that one makes will yield a lot of benefits that will return to oneself or the surroundings. The return of the benefits to the individual who makes educational investment is called the return to education. This study aimed to find out the return to education between male and female workers in West Java in 2014. The model employed was the Mincer earnings model. The data in the study were the secondary data from SAKERNAS 2014 with 14,951 selected samples. The analysis technique was multiple regression analysis. The results of the study showed that the educational level, work experience potential, work experience potential squared, and gender affect earnings. The higher the educational level was, the higher return to education was. The results of the chow test showed that there was a difference in the return to education between male and female workers. The female workers had the higher return to education than the male workers, except for the diploma education Keywords: return to education, workers, males, femalesAbstrak: Disparitas Gender dalam Tingkat Pengembalian Investasi Pendidikan di Jawa Barat. Investasi yang dilakukan seseorang akan membawa sejumlah manfaat yang kembali pada dirinya sendiri maupun pada lingkungan sekitar. Kembalinya manfaat pada individu yang melakukan investasi pendidikan sering disebut juga tingkat pengembalian investasi pendidikan. Penelitian ini bertujuan untuk mengetahui seberapa besar tingkat pengembalian investasi pendidikan antara tenaga kerja laki-laki dan perempuan di Jawa Barat Tahun 2014. Model yang digunakan adalah model persamaan pendapatan Mincer. Penelitian ini menggunakan data dari SAKERNAS dan diolah menggunakan teknik analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa tingkat pendidikan, potensi pengalaman kerja, potensi pengalaman kerja kuadrat dan jenis kelamin berpengaruh terhadap pendapatan. Semakin tinggi tingkat pendidikan maka tingkat pengembalian investasi pendidikan yang diterima pun semakin besar. Hasil chow test menunjukkan ada perbedaan tingkat pengembalian investasi pendidikan antara tenaga kerja laki-laki dan perempuan. Tenaga kerja perempuan menerima tingkat pengembalian investasi pendidikan lebih tinggi dibanding laki-laki, kecuali pada tingkat pendidikan Diploma.Kata kunci: Tingkat pengembalian investasi pendidikan, tenaga kerja, laki-laki, perempuan.